TINJAUAN SEMIOTIKA DALAM IKLAN TOYOTA - Andriyani, Putri; Rahayu, Nana; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Advertising is a message that connects advertisers with consumers. Anautomotive advertisement titled Toyota Doraemon is made in series using Doraemoncharacter. Toyota insert the advantages of its product in every scene and storyline. As amedium of information, advertisements are interesting to observe and disassemble thecontents of the message so that hidden meaning behind the signs is revealed throughPeirce’s semiotic theory. The method used is descriptive qualitative method. A data inthis study is collected non-verbal signs and classified based on icons, indexs, andsymbols. From reading the conversational dialogues in manga. The results isfounding behind the non-verbal signs in this advertisement, it contained productadvantages both functionally in the form of a car model and facilities and emotionallyeffect of the user.Key Word : Advertisements, Peirce’s Semiotic, Non-verbal Sign, Doraemon.